Strengthening woman-centred care for pregnant women with female genital mutilation in Australia: a qualitative muti-method study - Sabera Turkmani; Sabera Turkmani; Angela Dawson (Frontiers Media S.A., 2024)
Woman-centred care is a collaborative approach to care management, where the woman and her health provider recognise one another's expertise and interact based on mutual respect to provide adequate information and individualised care. However, woman-centred care has not been fully achieved, particularly for women who have experienced female genital mutilation in high-income countries. A lack of clear guidelines defining how to implement woman-centred care may negatively impact care provision. This study sought to explore the quality of point-of-care experiences and needs of pregnant women with female genital mutilation in Australia to identify elements of woman-centred care important to women and how woman-centred care can be strengthened during consultations with health professionals. This multi-method qualitative study comprised two phases. In phase one, we conducted interviews with women with female genital mutilation to explore their positive experiences during their last pregnancy, and in phase two, a workshop was held where the findings were presented and discussed to develop recommendations for guidelines to support woman-centred care. The findings of the first phase were presented under three distinct categories of principles, enablers, and activities following a framework from the literature. In phase two, narrative storytelling allowed women to share their stories of care, their preferences, and how they believe health providers could better support them. Their stories were recorded visually. This study highlights the importance of a comprehensive approach to woman-centred care involving experts, clinicians, community members, and women in designing education, tools, and guidelines.